JURIDICAL REVIEW OF THE CLAUSE OF WITHHOLDING THE ORIGINAL DIPLOMA OF WORKERS BY THE COMPANY IN THE EMPLOYMENT AGREEMENT - Kadek Debi Triwangsa Mahardika; Dewa Gede Pradnya Yustiawan (Transpublika Publisher, 2024)
The purpose of this research is to understand the aspects of legal certainty related to the Retention/Submission of Original Diplomas Clause in the employment contract applied by the Company and this research also aims to find out the legal protection efforts given to workers who agree to the retention of diploma clause in their employment contract, especially in the context where the Company is considered negligent in maintaining the original diploma belonging to its workers. The research method is normative legal research with an approach to legislation. The results of this study show that in the implementation of employment contracts that include diploma retention/submission clauses, there are no explicit statutory provisions that allow or prohibit the practice. However, regarding the legal requirements of agreements in employment contracts, this is regulated by the Civil Code. Therefore, the legal vacuum regarding whether or not the withholding of diplomas can cause this practice to occur as a result of customs in the world of work, and when related to RI Law No. 39 of 1999 concerning Human Rights is contrary to the principles of human rights because it hampers workers' rights to get better jobs and improve their quality of life. In addition, in the legal protection efforts for workers who agree to the clause of withholding/submission of diplomas in their employment contracts, there are preventive and responsive legal protections. This shows that there are measures to prevent and respond to potential violations of workers' rights in the context of such clauses.